Use of Paci and Alum to Reduce Tss Levels in People's Rubber Soaking Liquid Waste - Pratiwi, Larang; Irfa'i, Muhammad; Hamzani, Sulaiman; Santoso, Imam (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2024)
The coagulants used are PACl and alum because, in addition to their low price, PACl and alum are also proven to reduce turbidity and TSS levels in wastewater. This study aimed to determine the effect of PACl and alum on reducing TSS levels in people's rubber bath waste. This type of research is classified as an actual experiment, utilizing a pretest and posttest design with a control group. Integrated sampling was the sampling technique used in this study. Statistical analysis is performed using the normality test, and if the data is normally distributed, it is continued with the one-way ANOVA test. The normality test results showed average distributed TSS level data. They continued the Anova test (p = 0.005 < ɑ = 0.05), which found a difference between PACl and alum coagulant in reducing TSS levels in people's rubber immersion liquid waste. A PACl dose of 1200 mg/L lowered TSS levels by 46%. While the alum dose of 3000 mg/LL has not been able to reduce TSS levels, The variation in the dose of PACl and alum coagulants should be reduced again to be optimal for reducing TSS levels in liquid waste. To meet the quality standards of rubber immersion waste by reducing TSS levels, liquid waste with acidic or alkaline properties needs a neutralization process by adding lime.